Phase states of moisture content in different maize kernel types - Li, Na; Xu, Tongyu; Hao, Nan (International Journal of Agricultural and Biological Engineering, 2023)
ccurate determination of the moisture content in maize kernels conduces to screen maize germplasm materials with efficient dehydration. Low-field nuclear magnetic resonance (LF-NMR) single-kernel non-destructive testing technology was used to determine the moisture content at different phase states in the kernels for selected types of maize. The NMR T2 relaxation inversion spectrum was monitored in maize kernels to determine the variation in the moisture content in different phase states with time. The total water and free water peaked at the filling stage of the maize kernels and then declined to a minimum at physiological maturity. The semi-bound water generally increased to a long-lasting peak in the dough stage and then declined. The bound water increased from kernel formation to maturity and then remained stable. The contents of total water, free water, semi-bound water, and bound water had significant differences among kernel types but not among varieties of the same type. The contents of semi-bound water and free water were linearly correlated with the dehydration rates of the kernels. The results of this study can provide a means for creating new germplasm materials. Keywords: maize (Zea mays L.), LF-NMR, moisture phase state, kernel type, dehydration rate DOI: 10.25165/j.ijabe.20231601.7898 Citation: Li N, Xu T Y, Hao N. Phase states of moisture content in different maize kernel types. Int J Agric & Biol Eng, 2023; 16(1): 250–259.